Estudo fitoquímico biomonitorado de Duguetia lanceolata e Lithraea molleoides no controle de pragas agrícolas e processos de nanoencapsulamento - Domingues, Vanessa de Cássia (2016)
Leafcutter ants and maize weevil are responsible for great losses in Brazilian agriculture due to the difficult control of these pests. Natural products are becoming increasingly important, mainly in the search for non-toxic chemical compounds to humans, animals and environment and that can bio-rationally control agricultural pests’ behavior, such as insects and fungi. Different methods and new strategies have been the subject of studies to provide propositions for pest control. Among them, the search in nature for new compounds with insecticide and fungicide potential, as well as a synthesis of natural products derivatives with these properties. Accordingly, this study aimed the search of active fractions and compounds as regards the leafcutter ants Atta sexdens rubropilosa, its symbiotic fungus Leucoagaricus gongylophorus and Sitophilus zeamais, as known as maize weevil. Through bio-monitored phytochemical studies of the extracts of the plant parts of Duguetia lanceolata (Annonaceae) and Lithraea molleoides (Anacardeaceae), fractions with potential for pest control were found. The present study led to the isolation/identification of 19 substances, including some insecticide and fungicide emphasis. Current studies have been looking for new technologies for active ingredients application and nanoencapsulation seems to be a technique with great potential since systems for controlled release of substances controlling the stability of chemical actives can be found in it. Therefore, the other aspect of this work is related to the development of nanocapsules from biodegradable polymers for the nanoencapsulation of cedrelone, isolated from Trichilia catigua, as well as some semi-syntheses with the cedrelone limonoid, in the search of cedrelone derivatives to be tested on ants and fungi in order to enhance their fungicide and insecticide activities. For the large-scale isolation of cedrelone, present in T. catigua, the CCC technique (countercurrent chromatography) has proved to be successful, with some advantages, such as solvent and time savings, reproducibility and total sample recovery. During the development of formulations for nanoencapsulation, the nanoprecipitation technique proved to be both viable and reproducible for encapsulation. All formulations were stable and with high encapsulation efficiency. For cedrelone derivatives, cedrelone mesylate, propionate cedrelone and cedrelone acetate were synthesized and cedrelone propionate and cedrelone acetate showed great fungicide/insecticide potential against leafcutter ants.